Breakdown Voltage Using Bond Energy Calculation for CF3CHCl2/CO2 Mixture as Insulation Applied - Tedy Juliandhy; T. Haryono; Eka Firmansyah; Indra Perdana (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Sulfur hexafluoride gas according to the Montreal Protocol and Kyoto protocol needs to be limited and gradually reduced because it causes global warming, the greenhouse effect and acid rain on the environment. The Kyoto protocol recommends the use of dichlorotrifluoroethane gas as one of the alternatives to substitute sulfur hexafluoride gas. This research discusses the use of dichlorotrifluoroethane gas mixed with CO2 gas which was known to be able to withstand the breakdown voltage of 592-870 kV. Comparing to breakdown voltage predictions using methods based on bond energy, Paschen's law and high voltage tests. Breakdown voltage deviations using bond energy were better than Paschen's law. The dichlorotrifluoroethane gas economy has a price of 5.18 times cheaper than hexafluoride sulfur gas. The ability of dichlorotrifluoroethane gas to insulation gas in gas insulated switchgear needs to be applied as a real potential substitute for sulfur hexafluoride gas.Keywords- bond energy, dichlorotrifluoroethane, gas insulated switchgear, Paschen’s law, sulfur hexafluoride, techno-economy.